Matthew and the Didache : two documents from the same Jewish-Christian milieu? - Sandt, Huub van de, 1946- (Assen : Royal Van Gorcum ; Minneapolis : Fortress Press, 2005)
"There are significant agreements between the Didache and the Gospel of Matthew as these writings share words, phrases and motifs. In modern scholarship, there seems to be an increasing reluctance, however, to support the thesis that the Didache used Matthew. And, indeed, such a close relationship might equally suggest that both documents were created in the same historical and geographical setting, for example in the Greek-speaking part of Syria."--Jacket.
I Milieu -- Hypothesis on the development of Judaism and Christianity in Syria in the period after 70 C.E. / Bas ter Haar Romeny -- Milieu of Matthew, the Didache, and Ignatius of Antioch: agreements and differences / Clayton N. Jefford -- II. Two documents: their provenance and origin -- History and social setting of the Matthean community / Wim Weren -- When, why, and for whom was the Didache created? Insights into the social and historical setting of the Didache communities / Aaron
Includes bibliographical references (pages 243-263) and indexes.
English with some French.
Keywords: Bible. -- Criticism, interpretation, etc; Didache -- Criticism, interpretation, etc; Didache -- Criticism, Interpretation, etc